Odpowiedzi

2010-03-27T11:12:12+01:00
Wyraz ogólny dany jest wzorem:
a(n) = p + (n-1)*r
gdzie p jest pierwszym wyrazem
a r jest różnicą

wiemy, ze:
a(4) = 10
a(15) = 43

a(15)-a(4) = 43-10 = 33
ale:
a(15)-a(4) = p+14*r - p - 3*r = p - p +14r - 3r = 11r

Czyli 11r = 33
r = 3

a(4) = 10
oraz
a(4) = p + 3*r = p+3*3 = p+9
p+9 = 10
p = 1

Czyli ogólnie:
a(n) = 1 + 3*(n-1)

Suma pierwszych 45 wyrazów dana jest wzorem:
a(1)+...+a(45) =
45 * (a(1)+a(45))/2 = 45/2 * (1 + 1 + 44*3) =
= 45/2 * (2+132) = 45/2 * 134 = 45 * 134/2 = 45*66 = 2970